Outcome after tailored catheter ablation of atrial tachycardia using ultra‐high‐density mapping. (11th August 2020) - Jungen, Christiane; Akbulak, Ruken; Kahle, Ann‐Kathrin; Eickholt, Christian; Schaeffer, Benjamin; Scherschel, Katharina; Dinshaw, Leon; Muenkler, Paula; Schleberger, Ruben; Nies, Moritz; Gunawardene, Melanie A.; Klatt, Niklas; et al.
Abstract: Introduction: Tailored catheter ablation of atrial tachycardias (ATs) is increasingly recommended as a potentially easy treatment strategy in the era of high‐density mapping (HDM). As follow‐up data are sparse, we here report outcomes after HDM‐guided ablation of ATs in patients with prior catheter ablation or cardiac surgery. Methods and Results: In 250 consecutive patients (age 66.5 ± 0.7 years, 58% male) with ATs (98% prior catheter ablation, 13% prior cardiac surgery) an HDM‐guided catheter ablation was performed with the support of a 64‐electrode mini‐basket catheter. A total of 354 ATs (1.4 ± 0.1 ATs per patient; mean cycle length 304 ± 4.3 ms; 64% macroreentry, 27% localized reentry, and 9% focal) with acute termination of 95% were targeted in the index procedure. A similar AT as in the index procedure recurred in five patients (2%) after a median follow‐up time of 535 days (interquartile range (IQR) 25th–75th percentile: 217–841). Tailored ablation of reentry ATs with freedom from any arrhythmia was obtained in 53% after a single procedure and in 73% after 1.4 ± 0.4 ablation procedures (range: 1–4). A total of 228 patients (91%) were free from any arrhythmia recurrence after 210 days (IQR: 152–494) when including optimal usual care. Conclusions: Tailored catheter ablation of ATs guided by HDM has a high acute success rate. The recurrence rate of the index AT is low. In patients with extensive atrial scaring further ablation procedures need to be considered to achieve freedom from any arrhythmia.